Fisetin Attenuates Myocardial Ischemia-Reperfusion Injury by Activating the Reperfusion Injury Salvage Kinase (RISK) Signaling Pathway - Shanmugam, Karthi; Boovarahan, Sri Rahavi; Prem, Priyanka; Sivakumar, Bhavana; Kurian, Gino A (Frontiers in Pharmacology, 2021)
Ischemia-reperfusion (I/R) injury is an unavoidable injury that occurs during the revascularization procedures. In our previous study, we reported that fisetin a natural flavonoid attenuate I/R injury by suppressing mitochondrial oxidative stress and mitochondrial dysfunction. Fisetin is reported as a GSK3β inhibitor, but it remains unclear whether fisetin attenuates myocardial ischemia by activating the phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) pathway thereby inhibiting the downstream GSK3β or by directly interacting with the GSK3β while rendering its cardioprotection. In this study, we investigated the possible mechanism of action of fisetin while rendering its cardioprotective effect against myocardial I/R injury in rats. We utilized two myocardial I/R models in this study (i) Ligation of the left anterior descending artery and (ii) Langendorff isolated heart perfusion system; the latter has no neurohormonal influences. The PI3K inhibitor (Wortmannin, 0.015 mg/kg), GSK3β inhibitor (SB216763, 0.7 mg/kg), fisetin (20 mg/kg) was administered intraperitoneally before inducing myocardial I/R. Our result shows that the administration of fisetin decreased myocardial infarct size, apoptosis, lactate dehydrogenase, and creatine kinase in serum\perfusate of the rat hearts subjected to I/R. However, inhibition of PI3K with Wortmannin significantly reduced the cardioprotective effect of fisetin in both the ex vivo and in vivo models. The administration of GSK3β inhibitor after the administration of fisetin and Wortmannin, re-established the cardioprotection, indicate the major role of PI3K in fisetin action. Changes in myocardial oxidative stress and mitochondrial functional preservation of interfibrillar and subsarcolemmal mitochondria support the above findings. Hence here we report that fisetin conferred its cardioprotection against I/R injury by activating PI3K/Akt/GSK3β signalling pathway in rat hearts.